The Effectiveness of Coopertative Learning (STAD and PBL type) on E-learning Sustainable Development in Higher Education - Abd Syakur; Yulianto Sabat (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2020)
Development and application of educational technology in higher education with innovative learning models based on Cooperative Learning Type Student Teams-Achievement Divisions (STAD) and Project Based Learning (PBL). The purpose of this study is to analyze the educational technology model and innovative learning based on cooperative learning type STAD and PBL sustainable learning model innovation based on e-learning. This study focuses on the learning outcomes of TOEFL students in the Department of English Education in English courses at Brawijaya University Malang. Research methods using pre-test and post-test designs. Data analysis One Way ANOVA test and SEM analysis using Partial Least Square (PLS) software. The results of this study showed that the treatment of TOEFL tests (pre-test, mid-test, and post-test) in the control and experimental class with cooperative learning model type STAD and PBL were different. The average pre-test TOEFL score in the experimental class was 344.71 with a range of ??starting score 300-397 with standard deviation was 29.386. The average result of mid-test TOEFL score in experimental class was 345.46 with a range of ??ranging score from 300-380 with standard deviation was 20,587. The average post-test TOEFL score in experimental class was 360.83 with a range of ranging score from 303-400 with standard deviation was 24.146 (STAD and PBL p-value were 0.019 and 0.026, respectively). The results of development and application of innovative educational technology based on STAD and PBL e-learning could have significant influence on the result of student TOEFL score.